-f+10=-2f

Simple and best practice solution for -f+10=-2f equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -f+10=-2f equation:


Simplifying
-1f + 10 = -2f

Reorder the terms:
10 + -1f = -2f

Solving
10 + -1f = -2f

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '2f' to each side of the equation.
10 + -1f + 2f = -2f + 2f

Combine like terms: -1f + 2f = 1f
10 + 1f = -2f + 2f

Combine like terms: -2f + 2f = 0
10 + 1f = 0

Add '-10' to each side of the equation.
10 + -10 + 1f = 0 + -10

Combine like terms: 10 + -10 = 0
0 + 1f = 0 + -10
1f = 0 + -10

Combine like terms: 0 + -10 = -10
1f = -10

Divide each side by '1'.
f = -10

Simplifying
f = -10

See similar equations:

| -7x+6=-4x^2 | | 1.2x-3.5y=4 | | x+30+2=22 | | U(3v+2w)= | | 14.2=6.8+-4.2d | | 14.2=-6.8+-4.2d | | 3*(2x+8)=2*(2x-25) | | 1+4p=3p | | 50/62 | | 3x-13=x+59 | | v=r+pt | | 7(c-17)=-14 | | (x-6)(x+i)(x-i)(x-(6+i))(x-(6-i))=0 | | 4.4r+48.004=7.8(0.6r-1.82)-6.5r | | 7x+15-3=2x+7+4 | | 12(3n+0.7)=4(3n+2.1)+24n | | 10=-4t-6 | | 3p+5c=4p | | -8x-3y=22 | | (2a)^4/2a^4 | | 7x+13x-5=5(4x+4) | | (2a)4/2a4 | | -2x+12=-8+3x | | (3m-5n)/6-(3m-7n)/2 | | x^3-x^2-7x+3=0 | | 3(n+7)=9 | | 3-6x=6x+3 | | 50.00+3.75x=500 | | 11s+9s=20 | | R(s+3)= | | 1x^3-20x^2+81x-316=0 | | 1.5k=12x |

Equations solver categories